Dynamic voxel carving in tennis based on player localisation using a low cost camera network - Monaghan, D.; Kelly, P.; O'Connor, N. E. (Proceedings of the 18th IEEE International Conference on Image Processing (ICIP), 2011, 2011)
In this paper, we address the problem of reconstructing 3D volumetric models, illustrating human sporting performance for use in coaching scenarios. We advocate the use of low cost camera networks for acquiring such data, allowing the approach to be feasibly adopted by both amateur and elite level sports athletes. A dynamic voxel carving approach is described, coupled with over-head player tracking and autonomous background subtraction, to automatically produce a 3D reconstruction technique that intelligently uses memory resources. We demonstrate the efficacy of our approach in the context of tennis as a challenging application scenario.